CSR COMMUNICATION PT PERTAMINA IN LAND UTILIZATION HOME GARDENS AND THE ENVIRONMENT BABUL ULUM ISLAMIC BOARDING SCHOOL - Pipit Anggaeni; Desy Misnawati; Moh. Hafizni (Sean Institute, 2023)
The purpose of this research is to understand PT Pertamina's CSR Communication in the utilization of home gardens and the environment of the Babul Ulum Islamic Boarding School. Theoretical analysis uses the theory of innovation diffusion and community participation. The research method uses descriptive qualitative. Data collection is done through interviews, observation, and documentation. The results showed that the process of diffusion of innovation in